Rock-magnetic signature of precipitation and extreme runoff events in southeastern Patagonia since 51200 cal BP from the sediment of Lake Laguna Potrok Aike - Lisé Pronovost, A. (2014)
A 106-m long sediment sequence from the maar lake Laguna Potrok Aike in southern Patagonia was recovered in the framework of the International Continental Scientific Drilling Program (ICDP) Potrok Aike maar lake Sediment Archive Drilling prOject (PASADO). About half of the sedimentary sequence is composed of mass movement deposits (MMDs) and the event-corrected record reaches back to 51,200 cal BP. Here we present a high-resolution rock-magnetic study revealing two sedimentary facies associated with MMDs and characterized by two different types of spurious gyroremanent magnetization (GRM) acquired during static alternating field demagnetization. The first rock-magnetic signature is detected in MMDs composed of reworked sand and tephra material. The signature consists of GRM acquired during demagnetization of the natural remanent magnetization (NRM) and other rockmagnetic properties typical of iron sulfides such as greigite. We interpret these intervals as authigenic formation of iron sulfides in suboxic conditions within the MMD. The second rock-magnetic signature consists of a series of 10 short intervals located on the top of MMDs characterized by GRM acquisition during demagnetization of the isothermal remanent magnetization (IRM). Based on geological, limnological, stratigraphic and climatic evidence these layers are interpreted as reflecting pedogenic hematite and/or goethite brought to the lake by runoff events related to precipitation and permafrost melt. The pedogenic iron minerals mobilized from the catchment most likely settled out of suspension on top of MMDs after a rapid remobilization event. The series of runoff events corresponds to periods of increased lacustrine productivity in Laguna Potrok Aike and are coeval within the limit of the chronology to warm periods of the Last Glacial as recorded in Antarctica, the deglaciation in the mid-latitudes of the Southern Hemisphere and enhanced precipitation during the Early Holocene in southeastern Patagonia